The Innovation Capacity of the Electronic Traffic Law Enforcement (ETLE) of the Indonesian National Police Viewed by the Observatory of Public Sector Innovation (OPSI) Framework - Wiryawan Narendroputro; Effy Zalfiana Rusfian (Jurnal Public Policy, 2023)
Electronic Traffic Law Enforcement (ETLE) has been inaugurated and is expected to improve the image of the National Police, minimize extortion practices by officers, and increase driving discipline. Apart from that, ETLE is a National Police program to realize good governance with the values of transparency, accountability and responsiveness. This paper aims to analyze problems in the ETLE program using the Observatory of Public Sector Innovation (OPSI) Innovation Framework prepared by the Organization for Economic Co-operation and Development (OECD). The OPSI Framework consists of innovation objectives, potential, capacity, and impact. The analysis uses the OPSI Innovation Framework to identify problems that occur in innovation to carry out improvements and developments to create sustainable innovation. Based on the results of research using the OPSI framework, ETLE has several problems: requiring a lot of infrastructure with significant resources, an organizational culture that is still silo-like, community disobedience to rules and an organizational culture that is still traditional. The solution to this problem is: First, for limited infrastructure that requires a large budget, apart from collaborating with regional governments, the National Police can also request support from the central government to provide infrastructure for the implementation of ETLE throughout Indonesia because this is a priority program for the National Police; Second, the rules were not followed openly, the police had to carry out intensive information activities about ETLE and issue manual fines to deal with violations on the spot. Third, regarding organizational culture, the Police Chief, as the leader of the National Police, can create an innovative and agile corporate culture and implement collaborative governance with various stakeholders.